Synthesis of Isatin Derivatives Using Silver Nanoparticles as Green Catalyst: Study of Molecular Docking Interactions in SARS-CoV-2 3c-Like Protease and Determination of Cytotoxic Activities of the Compounds - Ponnusamy Packialakshmi (Hindawi Limited, 2021)
The coronavirus disease (COVID-19) is caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). As isatin-containing compounds exhibit several remarkable biological activities, isatin derivatives were prepared to combat the global pandemic caused by SARS-CoV-2 that is gripping the world. Herein, the synthesis of novel isatin derivatives has been reported. The cytotoxic activities of the compounds were determined using cancer cell (MCF-7) and normal cell (MCF-10A and MRC-5) lines. In silico molecular docking experiments were conducted using AutoDock Vina. We have successfully predicted the binding energies and the number of hydrogen bonds present. We have also identified the residues involved in hydrogen bond formation. The target compounds were synthesized using Schiff base following cyclization and Knoevenagel condensation reactions. We have focused on the recyclable synthesis of silver nanoparticles (AgNPs) using the extracts obtained from Dipteryx odorata. The extracts were used to reduce silver ions for the production of AgNPs. The synthesized nanoparticles exhibited excellent catalytic activities during the synthesis of isatin derivatives in ethanol. The formation of the target isatin derivatives has been confirmed using the Fourier transform-infrared (FT-IR), proton nuclear magnetic resonance (1H NMR) spectroscopy, 13C NMR spectroscopy, mass spectrometry, and elemental analysis techniques. Compound 3e was found to be the most active compound when tested against the MCF-7 cancer cell line (IC50=20.5 μM). The activity was comparable to the activities of standard doxorubicin and other compounds. In silico molecular docking experiments were conducted to study the spike protein in SARS-CoV-2 (PDB ID: 6LU7). Compound 3c exhibited high binding ability (−9.4 kcal/mol). The inhibition ability was studied using hydroxychloroquine as a standard. Results from docking studies revealed that the inhibition ability of compound 3c was higher than the inhibition abilities exhibited by other compounds. The synthesized compound 3e is a potential antiviral drug that can be used for treating the COVID-19 disease.